1979
DOI: 10.1172/jci109349
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic-physiologic correlates of the severity of fibrosis and degree of cellularity in idiopathic pulmonary fibrosis.

Abstract: A B S T R A C T Idiopathic pulmonary fibrosis (IPF) is a progressive disease of lung parenchyma characterized by a chronic inflammatory cellular infiltration and varying degrees of interstitial fibrosis. Current data indicate that the severity of fibrosis and the degree of cellularity determine, in part, the prognosis of IPF and the response to therapy. Whereas lung biopsy gives the best assessment of fibrosis and cellularity, physiologic studies are used to stage and monitor the disease process. To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
2
4

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(104 citation statements)
references
References 37 publications
6
92
2
4
Order By: Relevance
“…This may explain the low DL,CO and CL,s in the present patients with stage I sarcoidosis (low DL,CO in 13% and low CL,s in 17%). In previous studies, a reduced CL,s was frequently observed in ILD patients with reduced lung volumes [32][33][34][35][36]. However, in only one study was lung compliance measured in patients with ILD but normal lung volumes [37].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the low DL,CO and CL,s in the present patients with stage I sarcoidosis (low DL,CO in 13% and low CL,s in 17%). In previous studies, a reduced CL,s was frequently observed in ILD patients with reduced lung volumes [32][33][34][35][36]. However, in only one study was lung compliance measured in patients with ILD but normal lung volumes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Again, as for COPD, there are certain exercise response characteristics that are suggestive of ILD, although the diagnosis of ILD is rarely made with exercise testing. Pulmonary gas-exchange abnormalities during exercise may be the only physiological alteration evident in ILD [114,115].…”
Section: Arterial Oxygen Desaturation During Exercisementioning
confidence: 99%
“…Crystal and colleagues reported "good" correlation between fibrosis and the coefficient of retraction and the change in exercise Pa O 2 and P(a-a) O 2 but a "poor" correlation with spirometry, lung volumes, Dl CO , and resting gas exchange in 18 patients with IPF (22). In a more detailed analysis, Fulmer and colleagues provided a semiquantitative histologic description of 23 patients with IPF (6). Almost all parameters of lung distensibility correlated with the extent of fibrosis, although not with cellularity.…”
Section: Can Pulmonary Function Testing Establish Disease Severity?mentioning
confidence: 99%
“…Lung recoil is increased over the range of the inspiratory capacity with a reduction of total lung capacity (TLC) and vital capacity (VC) (3)(4)(5), whereas the coefficient of retraction (pleural pressure at TLC/lung volume at TLC) is elevated compared with normal subjects (3,6). As a result of these changes, static lung volumes are typically reduced in DPLDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation